Prilaku Homoseksual Komunitas Mua Banjarmasin dan Komunikasi Persuasif sebagai Upaya Pencegahan Penyakit Menular Seksual Melalui Penyuluhan Kesehatan - Arizal Arizal; Gita Gita; Irwansyah Irwansyah; Iib Kurnianti; Marhaeni Fajar Kurniawan (Jurnal Health Sains, 2021)
Homosexual is a taboo word that is spoken by many people. This deviant behavior due to environmental factors. Homosexual behavior is also closely related to HI-Aids. The authors feeling need t take a personal approach to find out more about the lives of homosexuals in Banjarmasin and the sexually transmitted diseases that overshadow them in order to prevent the spread of deviant sexual behavior. This study aims to determine the causes of deviant sexual behavior in the MUA Banjarmasin community and forms of prevention with health education about the dangers of deviant sexual behavior. This type of research is descriptive with a qualitative approach. The research respondents were the MUA community in Banjarmasin city and carrier out in June 2021. The result showed that same-sex deviant sexual behavior had occurred in the MUA Banjarmasin community. They are very aware of the diseases risk faced when having sex with the same-sex. But they think the diseases comes from themselves as long as they can take care of themselves so they can reduce the transmission risk. Researchers conclude that several factors trigger the formation of same-sex sexual behavior due to environmental factors, errors in parenting patterns, excessive same-sex interactions, and stress due to work pressure. To raise awareness of the deviant behavior of members Banjarmasin MUA community, it is necessary to carry out health education as a form of communication. The extension model that can be implemented is two-way communication such as question and answer of discussion.